School - Based Assessment: the interface between Continuous Assessment (CASS) and the external summative examination at Grade 12 level with special focus on Mathematics and Science - Howie, Sarah J. (University of Pretoria, 2013)
Dissertation (MEd (Assessment and Quality Assurance))--University of Pretoria, 2005.